Burn injury characteristics and outcomes among pediatric and adult patients admitted to Ministry of National Guard Health Affairs (MNGHA) hospitals in Saudi Arabia - Abrar M. Al-Mutairi; Safiah Labani; Manar J. Alasmari; Muhammed S. Alamri; Abdullah S. Alqahtani; Ibrahim Albabtain; David G. Greenhalgh (Elsevier, 2023)
Objective: This study aims to describe the characteristics and outcomes of burn injuries in pediatric and adult patients admitted to Ministry of National Guard Health Affairs (MNGHA) hospitals in Saudi Arabia. Methods: A multicenter retrospective cohort study was conducted between 2015 and 2021 in five hospitals run by the MNGHA in Saudi Arabia. The study included 555 patients who were admitted to the hospital with burns, and data were collected from an institutional trauma registry on various aspects such as sociodemographic variables, burn clinical characteristics and burn outcomes. The differences in epidemiological data, general characteristics, and outcomes of burn patients with ≤18 and >18 years of age among Saudi hospitalized patients. The associations between patient characteristics and burn outcomes were assessed using multivariable logistic regression. Results: Most of the participants representing 66.1% males and females 33.9%. Flame and contact were the most common causes of burn injuries, accounting for 43.6% and 43.2% of cases, respectively; followed by chemical (6.7%), then electrical (5.4%), and friction (1.1%). The study revealed that pediatric were the most frequently admitted age group for burn injuries with most cases occurring at home (57%). Pediatric patients had a higher percentage of hot fluid injuries, accounting for 77.5 % of cases (P = 0.00). Flame injuries were more prevalent in adults, accounting for 65.3% of cases (P < 0.05). The study reported that there were significant associations between age, gender, % TBSA, body region affected, and inhalation injury with admission to the ICU in patients with burn injuries. Relative to patients with third degree burns, first and second-degree burns were associated with a lower likelihood of mortality (OR 0.13, 95% CI: 0.03,0.51, p = 0.00). Conclusion: The study's findings can be utilized to aid in the implementation of different prevention programs and allocate appropriate resources for treatment to reduce the incidence and morbidity of burn injuries. It is essential to continue educating the public on fire safety in the home environment. This can help raise awareness, promote household safety precautions, and encourage early medical care seeking.